A DEEP YEARNING FOR DOING SOMETHING? HOW TO FIND ‘BRAND NEW’ GOALS AND WISHES? IN JUST FOUR WAYS, A PERSON GAINS FASCINATING INSIGHT INTO LIFE WITH A STRONG DRIVE! - Turdaliyeva Mokhlaroyim Maxammadismoil qizi (Journals Park Publishing, 2022)
The article presents information about four ways to find new goals and desires to do what a person wants. It explains how a human body, ‘miniscule’ details of life, a mindset and, finally, a void – an empty room in a person’s mind are all-important points in finding new goals and wantings.
Keywords: a body, a ‘wanting’ muscle, miniscule things, a mind, a void.